Instrumented measures of postural control in college dancers with and without chronic ankle instability. (November 2022) - Parks, Ashlee; Gosselin, Sarah; Goetschius, John
Abstract: Objectives: To determine whether collegiate dancers with chronic ankle instability (CAI) demonstrated impaired postural control during instrumented measures of single-leg static balance compared to dancers without CAI. Design: Cross sectional design. Setting: University dance studios. Participants: We included N = 39 dance majors from a large, public university. We stratified participants into CAI (n = 20, age = 20 ± 1.8, IdFAI = 17.3 ± 5.7, number of sprains = 1.9 ± 1.1) and Control groups (n = 19, age = 20 ± 1.2, IdFAI = 2.5 ± 3.0). Main outcome measures: Participants performed 3 x 10-s single-leg, static balance trials on a pressure mat in two different conditions, foot-flat eyes closed and demi-pointe eyes open. We measured six different time-to-boundary (TTB) measurements during each balance trial and calculated the average of the 3 trials for each condition. Participants also completed the Foot and Ankle Ability Measure (FAAM) sport and activities of daily living (ADL) questionnaires. Results: The CAI group reported greater IdFAI and lower FAAM-ADL and FAAM-Sport scores compared to the control group. We observed no significant differences in TTB measurements between the CAI and control groups during either balance conditions. Conclusions: Instrumented measures of static postural control were not impaired in college dancers with CAI compared dancers without CAI. Highlights: 52% of college dancers in sample met the criteria for chronic ankle instability. College dancers with chronic ankle instability reported poorer ankle function. Postural control was not impaired in college dancers with chronic ankle instability. Dance may mitigate the effects of chronic ankle instability on postural control.